2020
DOI: 10.3390/catal10101188
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Reactivity of Carbon–Nitrogen–Sulfur-Doped TiO2 Upconversion Phosphor Composites

Abstract: Sol–gel synthesized N-doped and carbon–nitrogen–sulfur (CNS)-doped TiO2 solutions were deposited on upconversion phosphor using a dip coating method. Scanning electron microscopy (SEM) imaging showed that there was a change in the morphology of TiO2 coated on NaYF4:Yb,Er from spherical to nanorods caused by additional urea and thiourea doping reagents. Fourier transform infrared (FTIR) spectroscopy further verified the existence of nitrate–hyponitrite, carboxylate, and SO42− because of the doping effect. NaYF4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The absorption bands at 3421 and 1575 cm –1 were assigned to the stretching vibrations of the O–H and CO groups, respectively . The band at 699 and 1120 cm –1 were associated with the stretching vibrations of the C–S and SO bonds, respectively . Raman spectroscopy was applied to complement our insights into the phase structure (Figure b).…”
Section: Results and Discussionmentioning
confidence: 99%
“…The absorption bands at 3421 and 1575 cm –1 were assigned to the stretching vibrations of the O–H and CO groups, respectively . The band at 699 and 1120 cm –1 were associated with the stretching vibrations of the C–S and SO bonds, respectively . Raman spectroscopy was applied to complement our insights into the phase structure (Figure b).…”
Section: Results and Discussionmentioning
confidence: 99%
“…In the study of Eun et al [5], sol-gel-synthesized N-doped and carbon-nitrogensulfur (CNS)-doped TiO 2 solutions were deposited on upconversion phosphor using a dip-coating method. Scanning electron microscopy (SEM) imaging showed that there was a change in the morphology of TiO 2 coated on NaYF 4 :Yb,Er from spherical to nanorods caused by additional urea and thiourea doping reagents.…”
Section: Tio 2 -Based Photocatalystsmentioning
confidence: 99%